Relational Analysis of Knowledge and Adoption of Organic Farming Practices in Gujarat State (Indian Journal of Extension Education, 2016)
Organic agriculture may be considered as a development vehicle for developing countries like India, in particular with this context research study was undertaken for 180 farmers in capacity building of farmers through training on organic farming practices in Surendranagar, Jamnagar and Rajkot district of Gujarat state. The results shows that majority of trained and untrained farmers had medium level of knowledge and medium level of adoption about organic farming practices. Among all the variables education, extension participation, organic farming experience, localite cosmopolite value orientation, risk orientation, scientific orientation had positive and significant association with the knowledge and adoption of organic farming practices in both trained and untrained farmers. While in addition to this trained farmers’ had also positive and significant association with social participation, innovativeness and mass media exposure, market of organic produce and herd size.